2017
DOI: 10.3389/fimmu.2017.01248
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Chemokine CXCL7 Dimer Preferentially Exists in the Glycosaminoglycan-Bound Form: Implications for Neutrophil–Platelet Crosstalk

Abstract: Platelet-derived chemokine CXCL7 (also known as NAP-2) plays a crucial role in orchestrating neutrophil recruitment in response to vascular injury. CXCL7 exerts its function by activating the CXC chemokine receptor 2 (CXCR2) receptor and binding sulfated glycosaminoglycans (GAGs) that regulate receptor activity. CXCL7 exists as monomers, dimers, and tetramers, and previous studies have shown that the monomer dominates at lower and the tetramer at higher concentrations. These observations then raise the questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 50 publications
0
51
1
1
Order By: Relevance
“…CXCL7, also known as NAP‐2, is secreted from α‐granules upon platelet activation, and when it binds to its receptor, CXCR2, it plays important roles in regulating inflammation. It is a truncation product of the platelet‐derived connective tissue‐activating peptide III and is crucial in orchestrating neutrophil recruitment in response to vascular injury and neutrophil‐platelet crosstalk 30,31 . Previous studies had shown increased serum levels of CXCL7 in atherosclerosis, critical limb ischemia, and various malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL7, also known as NAP‐2, is secreted from α‐granules upon platelet activation, and when it binds to its receptor, CXCR2, it plays important roles in regulating inflammation. It is a truncation product of the platelet‐derived connective tissue‐activating peptide III and is crucial in orchestrating neutrophil recruitment in response to vascular injury and neutrophil‐platelet crosstalk 30,31 . Previous studies had shown increased serum levels of CXCL7 in atherosclerosis, critical limb ischemia, and various malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…26 NAP-2 is another cytokine with high levels in platelets, attributed to play a significant role for neutrophil recruitment in response to vascular injury. 27 RANTES represents a chemotactic mediator for monocytes, eosinophils, and T-cells triggering cytokine synthesis in key effector cells. 28 The concentrations of these chemokines were measured in PRP and in the medium of WP after incubation for 30 minutes with 15 µg/mL Pam3CSK4 or with 15 µg/mL LPS (►Fig.…”
Section: Platelet Activation Induces a Rapid And Persistent Upregulatmentioning
confidence: 99%
“…Furthermore, these studies show not only basic residues that are conserved but also those that are unique to a given chemokine mediate binding. [30][31][32][33][34] Most interestingly, these chemokines show a diversity of GAG-binding surfaces, indicating chemokine-specific residues play an important role in dictating the binding interactions, and that location and distribution of both conserved and chemokine-specific residues in the context of three-dimensional structure determine binding geometry. Residues implicated in binding are highlighted, and those that are conserved (in at least five out of seven sequences) are in red and shaded in gray and are labeled from B1 to B8.…”
mentioning
confidence: 99%
“…Furthermore, heparin-bound CXCL1 and CXCL7 are unable to bind the CXCR2 N-terminal peptide. 30,31 Heparin-bound CXCL8 and CXCL7 have also been shown to be impaired for receptor activity. 30,45 These studies collectively suggest that it is the free chemokine and not GAG-bound chemokine that can access the receptor and, by extension, it is the chemotactic gradients that drive neutrophil egress from the vasculature to the target tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation